Pediatric intramedullary schwannoma with syringomyelia: a case report and literature review - Keda Wang; Jizong Zhao; Yan Zhang; Yibing Su (BMC, 2018)
Abstract Background Intramedullary schwannomas without neurofibromatosis are exceedingly rare. They are rarer in children with only 8 cases reported so far. The association of intramedullary schwannomas with syringomyelia is also rare. Here, we present a case of intramedullary schwannoma with syringomyelia treated surgically in an 9-year-old boy. Case presentation We reviewed the clinical course of a 9-year-old boy, who presented with both lower extremity weakness of 6-month duration. Neurophysical examination revealed a decreased sensation below the T10 dermatome. Magnetic resonance imaging (MRI) showed an well-demarcated intramedullary lesion located at the level of T8 vertebra with isointensity on T2WI and hypointensity on T1WI, which was homogeneous enhanced after gadolinium injection. There was associated syringomyelia extending from T7 down to the level of T10. A mild scoliotic deformity was also observed. The lesion was totally resected after an T7-T8 laminoplasty. Histopathological findings were consistent with schwannoma. Postoperative MRI did not reveal the presence of a residual tumor with syringomyelia reducted. By 2 weeks after treatment, the patient had experienced nearly complete recovery. Management with external bracing was performed on this patient for 3 months after surgery to prevent spinal deformity. However, mild spinal kyphosis occurred 5 months after surgery, and a progressive postoperative spinal kyphosis was observed during these 3 years of follow-up. Continued conservative management with observation was performed as there is no association with functional decline and impairment in health-related quality-of-life measures. Conclusion Although extremely rare and uncommonly associated with syringomyelia, schwannomas need to be considered in the preoperative diagnosis of solitary intramedullary tumors in children as total resection can be achieved improving surgical outcome; Pediatric patients should be monitored closely for the development of spinal deformity following resection of intramedullary schwannoma, particularly possessing preoperative scoliotic deformity and/or tumor-associated syringomyelia.